Kajian Waktu Etsa dan Penurunan Massa PCB double Layar - Budiana Budiana; Elin Aprilia; Mchael Timanta Ginting; Budi Sugandi (Politeknik Negeri Batam, 2018)
FeCl3 Etching is the process of removing certain parts of a material using FeCl3 with a minimum concentration of 28%. The method used with FeCl3 solution is a chemical reaction method and material etched is PCB. This study aims to determine the effect of 3 variations used on PCB mass reduction and etching time. Characterization variation used is PCB plate etched using heating and stirrer (PS), PCB plate etched using heating without using stirrer (PTS) and PCB plate etched without using heating and stirrer (TPTS). After the etching process, the PCB plate is characterized using optical microscopy. Based on the research, the mass reduction value of PS is highest for all variations and the etching time of PS occurs at 5 minutes is the fastest than the PTS (10 minutes) and TPTS (20 minutes).